Handbook for focus on adult health : medical-surgical nursing - Mann, Andrea Rothman (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2013)
A clinical reference that presents need-to-know information on over 170 commonly encountered diseases and disorders. It enables readers to gain quick access to vital information on Pathophysiology, Risk Factors, Clinical Manifestations and Assessments, Diagnostic Methods, and, Medical and Nursing Management Complications